Glutamine synthetase 2 is not essential for biosynthesis of compatible solutes in Halobacillus halophilus - Shiyan, Anna; Thompson, Melanie; Köcher, Saskia; Tausendschön, Michaela; Santos, Helena; Hänelt, Inga; Müller, Volker (Frontiers in Microbiology, 2014)
Halobacillus halophilus, a moderately halophilic bacterium isolated from salt marshes, produces various compatible solutes to cope with osmotic stress. Glutamate and glutamine are dominant compatible solutes at mild salinities. Glutamine synthetase activity in cell suspensions of H. halophilus wild type was shown to be salt dependent and chloride modulated. A possible candidate to catalyze glutamine synthesis is glutamine synthetase A2, whose transcription is stimulated by chloride. To address the role of GlnA2 in the biosynthesis of the osmolytes glutamate and glutamine, a deletion mutant (ΔglnA2) was generated and characterized in detail. We compared the pool of compatible solutes and performed transcriptional analyses of the principal genes controlling the solute production in the wild type strain and the deletion mutant. These measurements did not confirm the hypothesized role of GlnA2 in the osmolyte production. Most likely the presence of another, yet to be identified enzyme has the main contribution in the measured activity in crude extracts and probably determines the total chloride-modulated profile. The role of GlnA2 remains to be elucidated.